Energy efficient power amplifier design for next generation mobile handsets - Sajedin, Maryam (2023)
The Power Amplifier (PA) is an essential RF component for wireless communication systems to achieve small, reliable, and low cost transmitters. Hence, efficiency enhancement of PA over a wide range of output power levels is crucial in high-capacity microwave radios, where the thermal issues are critical due to the compact nature of the radio module configuration. The Doherty power amplifier (DPA) with improved power-added efficiency at backed off power levels and ease of additional linearization is widely deployed in base-stations to deal with modern communication signals with high peak-to-average power ratios. However, DPAs in practice have often failed to exhibit the superb efficiency predicted by theory, its narrowband performance can not satisfy the bandwidth requirement of modern radios that need to support multiple standards and backward compatibility. Therefore, research efforts on DPA have been targeted towards enhancing the efficiency and linearity, and beyond that extending the operating bandwidth for millimeter wave frequencies. This contribution targets to develop a novel dynamic load modulation DPA circuity for mobile handset application that can provide an optimum compromise between linearity and efficiency while covering multiple cellular frequency bands, including the 5G frequency band. To achieve these goals, this dissertation firstly provides a concrete survey on DPA, highlighting key developments for complex modulation standards, coupled with practical challenges and limitations. Furthermore, the efficiency improvement of a GaN HEMT Class-F configuration is experimentally validated for sub 6GHz. The work is further elaborated by designing a DPA based on the wave-shaping networks, including the harmonic control circuits. The proper load impedance for the second and third harmonics were selected that enhanced the efficiency and compensated the low current drive of the peaking device in the conventional DPA. Moreover, in this thesis, a wideband 1W Class-J PA is designed and fabricated based on the discrete die GaN on SiC HEMT Qorvo’s TQGaN25 process. The measured results show excellent performance of the PA. The work is extended by designing a DPA incorporating Class-J mode of operation that utilizes the transistors’ parasitic capacitance for wider bandwidth. The final contribution in this thesis is to harness GaAs (D-Mode) pHEMT monolithic integration technology to combat two main mobile handset PA challenges: efficiency-bandwidth for mm-wave frequencies and compact area size. A systematic wideband design procedure of a fully integrated 1W MMIC DPA architecture supported by advanced model and circuit design theory was proposed and validated by EM simulation analysis at mm-wave frequencies. The transformer ratio of the DPA at higher frequencies, where the optimum impedance at output are too small, was reduced by the post-matching network. Finally by adding the second-harmonic voltage component at the drain node of the main PA, a high efficiency over the band frequency was achieved.